Formulasi dan Evaluasi Gel Pelembap Ekstrak Mesokarp Semangka [Citrullus lanatus (Thunb.) Matsum. & Nakai] sebagai Antioksidan - Sari Defi Okzelia; Waffiyyatul Mardiyyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Dry skin is the most common skin problem, so moisturizers are used to prevent it. White skin (mesocarp) of watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai] (MW) has the potential to be formulated into a moisturizing gel preparation since it contains vitamins and citrulline which also possess antioxidant activity. This study aimed to formulate a moisturizing gel preparation from MW extract as an antioxidant. MW was extracted by maceration using 70% ethanol and formulated into moisturizing gel preparation at concentrations of 5% (F1), 10% (F2), and 15% (F3). Gel preparations were evaluated physically, and determined their moisture content and antioxidant activity. MW extract was a brown color with 25.02% yield. The evaluation results showed that all formulations met the standard parameters of good gel preparations including organoleptic, homogeneity, spread-ability, adhesion, pH, and viscosity, and did not irritate the skin. The skin moisture after application of F1, F2, and F3 respectively were 29.49%; 36.63%; and 43.48%. IC50 values for F1, F2, and F3 respectively were 156.42; 149.24, and 138.05 µg/mL. The moisturizing gel preparation from MW extract met all the standard parameters of good gel preparation, could increase the percentage of skin moisture, and had moderate antioxidant activity.